(untitled) (Scientific journal of the Fergana State University, 2025)
This article analyzes the methods, goals, and objectives of physical training for students in general education schools, as well as the forms and methods of physical education for children in educational institutions. Acquiring the skill of independent practice, not only during lessons but also as part of or during a portion of the lesson, has a positive impact on the effectiveness of the educational process and serves as a foundation for the individual’s level of physical education.